2021
DOI: 10.1108/jeas-09-2020-0158
|View full text |Cite
|
Sign up to set email alerts
|

Insurance and economic growth in Ghana

Abstract: PurposeThe Ghanaian insurance industry has been transformed significantly from state-led to a market-driven one over the past decades. The empirical literature on the causal relationship between insurance and economic growth has been mixed, but little study on this has been done in Ghana. This study therefore empirically examines the effect of the growing insurance industry on the economic growth in Ghana.Design/methodology/approachQuantitative research design was deployed in the study. The study used Johansen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 68 publications
(105 reference statements)
2
1
0
1
Order By: Relevance
“…This conclusion is consistent with findings of Akinsola and Odhiambo (2017) [5]. In a recent study, Osei-Bonsu et al (2021) [26] found a long-term inverse relationship between Ghana's inflation and economic growth.…”
Section: Results Of Long Run Analysissupporting
confidence: 90%
“…This conclusion is consistent with findings of Akinsola and Odhiambo (2017) [5]. In a recent study, Osei-Bonsu et al (2021) [26] found a long-term inverse relationship between Ghana's inflation and economic growth.…”
Section: Results Of Long Run Analysissupporting
confidence: 90%
“…In particular, a short-term increase in INS would result in a decrease in GDP of 0.426467 units, whereas a long-term increase in INS would result in an increase in GDP of 0.355074. This supports previous research (Mainata & Pratiwi, 2019;Mohy ul din et al, 2017;Muye & Hassan, 2016;Osei-Bonsu et al, 2021). The negative effect in the short term occurs because more than 80% of the sharia insurance investment portfolio is placed in the Islamic capital market with high volatility.…”
Section: Effect Of Sharia Insurance Growth On Indonesia's Economic Gr...supporting
confidence: 90%
“…The financial sector is related to economic growth through its function of distributing funds to sectors in need so that a developing financial sector will strengthen the allocation of sources of funds for 141 p-ISSN: 2503-4235 economic growth. Furthermore, research on the Islamic financial industry is still very limited, as the majority of existing studies only look at the financial industry in the stock/capital market sector (Kapaya, 2020;Tan & Shafi, 2021), banking (Anwar et al, 2020;Elmawazini et al, 2020;Ledhem & Mekidiche, 2020;Supriani et al, 2021), bonds Smaoui & Nechi, 2017), and the insurance industry (Mainata & Pratiwi, 2019;Muye & Hassan, 2016;Osei-Bonsu et al, 2021) separately.…”
Section: Introductionmentioning
confidence: 99%
“…Adanya regulasi asuransi mandatory yang dinamis di internal pemerintah, dalam hal ini BPJS Kesehatan, Jasa Raharja, BPJS Kesehatan memberikan peluang kepada Mandiri Inheath untuk tetap align dan sejalan dengan produk wajib yang dikeluarkan oleh pemerintah [15]. Dalam satu sisi, Mandiri Inhealth dituntut untuk lebih memberikan fleksibilitas dalam hal layanan bagi pesertanya, disisi lain Mandiri Inhealth juga dituntut comply dan tetap mematuhi regulasi BPJS kesehatan, Jasa Raharja maupun BPJS Ketenagakerjaan sehingga produk yang direlease tetap beririsan dengan BPJS Kesehatan [16].…”
Section: Pendahuluanunclassified